Pengaruh Edukasi Body Shaming terhadap Tingkat Pengetahuan Remaja - Sabrina Azzahro Putri; Qomariah Qomariah; Widya Mariyana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Body shaming represents a global issue shaped by social constructions and media portrayals of the human body. Individuals who experience body shaming often feel humiliated and intimidated, leading to low self-image and diminished gratitude for their bodies. This study aimed to examine the effect of body shaming education on adolescents’ knowledge levels at SMP Futuhiyah Mranggen. The research employed a quasi-experimental design with a one-group pretest–posttest approach. The population included all 41 male and female seventh-grade students, selected through total sampling. Researchers used a validated knowledge questionnaire delivered through a PowerPoint presentation as the data collection instrument. Data analysis applied the Wilcoxon test. The conclusion of this study is that there is an influence of body shaming education on the level of knowledge of adolescents at SMP Futuhiyah Mranggen with a p-value of 0.000 because it is less than 0.05. The suggestion that will be put forward is that it is hoped that all adolescents can increase their understanding of body shaming, to find out the level of knowledge about body shaming in adolescents who are given intervention, and awareness of the impact of body shaming and handling of body shaming in adolescents at SMP Futuhiyah Mranggen, adolescents who are given education related to body shaming and surrounding adolescents.